Pengaruh Tingkat Responsivitas Pemerintah Daerah terhadap Kepuasan dalam Penanganan Pengaduan Masyarakat pada Kanal Sambat Online Kota Malang - Muhammad Farrel Langit Arundaya; Muhammad Farid Ma'ruf; Fitrotun Niswah; Galih Wahyu Pradana (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the effect of local government responsiveness in handling online public complaints through SAMBAT Online on community satisfaction. The research employed a quantitative approach with a causal associative design. Data were collected from 90 respondents who had previously used SAMBAT Online services. Data analysis techniques included descriptive statistics, instrument testing, classical assumption tests, simple linear regression, t-test, and coefficient of determination analysis using SPSS version 25. The results indicate that the responsiveness level of the Malang City Government is categorized as moderate with a percentage score of 64.09%, while community satisfaction is categorized as high with a score of 69.96%. Simple linear regression analysis revealed that responsiveness has a positive and significant effect on community satisfaction, indicated by a significance value of 0.000 0.05 and a coefficient of determination (R²) of 0.524. This finding suggests that government responsiveness contributes 52.4% to community satisfaction, while the remaining 47.6% is influenced by other factors outside the research model. The study concludes that responsiveness is a crucial determinant in improving public satisfaction with digital complaint services.